Prevalence and risk factors of intestinal protozoan infection among child students with disabilities in Bantul District, Yogyakarta Special Region, Indonesia - Fahriana Azmi; Elsa Herdiana Murhandarwati; Mahardika Agus Wijayanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Children with disabilities are excluded from many aspects of life. Unfortunately, they have an increased risk of infection from many kinds of pathogens including intestinal protozoan. This study aimed to determine the prevalence of intestinal protozoan infections and to evaluate the associated factors among children with disabilities in Bantul District, Yogyakarta Special Region, Indonesia. A cross-sectional study was conducted at school with special needs between June-December, 2019. A total of 150 participants were recruited through simple random sampling. Stool samples were examined microscopically by formalin-ether concentration and Ziehl-Neelsen staining technique. Age was analyzed using the Mann-Whitney tests, while the other variables used chi-square tests. Multivariable logistic regression was conducted to identify factors associated with intestinal protozoan infections. The adjusted prevalence ratio with a 95% confidence interval at a 5% level of significance was used to measure the strength of association. Overall, there were 15 children infected by intestinal protozoan among 130 subjects with mean age of participants of 9.83 ± 3.1 years. The intestinal protozoan species were Entamoeba histolytica 7 (5.38%), Giardia lamblia 4 (3.08%), Blastocystis hominis 7 (5.38%) and Iodamoeba butschlii 1 (0.77%). Prevalence of intestinal protozoan infection among children with disabilities in Bantul District, Yogyakarta, Special Region was 11.54%. There were no significant correlations between the risk factors and intestinal protozoan infection among children with disabilities (p>0.05).